Nitrification and Autotrophic Nitrifying Bacteria in a Hydrocarbon-Polluted Soil - Deni, Jamal (American Society for Microbiology, 1999)
In vitro ammonia-oxidizing bacteria are capable of oxidizing hydrocarbons incompletely. This transformation is accompanied by competitive inhibition of ammonia monooxygenase, the first key enzyme in nitrification. The effect of hydrocarbon pollution on soil nitrification was examined in situ. In a microcosm study, adding diesel fuel hydrocarbon to an uncontaminated soil (agricultural unfertilized soil) treated with ammonium sulfate dramatically reduced the amount of KCl-extractable nitrate but stimulated ammonium consumption. In a soil with long history of pollution that was treated with ammonium sulfate, 90% of the ammonium was transformed into nitrate after 3 weeks of incubation. Nitrate production was twofold higher in the contaminated soil than in the agricultural soil to which hydrocarbon was not added. To assess if ammonia-oxidizing bacteria acquired resistance to inhibition by hydrocarbon, the contaminated soil was reexposed to diesel fuel. Ammonium consumption was not affected, but nitrate production was 30% lower than nitrate production in the absence of hydrocarbon. The apparent reduction in nitrification resulted from immobilization of ammonium by hydrocarbon-stimulated microbial activity. These results indicated that the hydrocarbon inhibited nitrification in the noncontaminated soil (agricultural soil) and that ammonia-oxidizing bacteria in the polluted soil acquired resistance to inhibition by the hydrocarbon, possibly by increasing the affinity of nitrifying bacteria for ammonium in the soil.